A radionuclide outlier identification and correlation analysis on low- and intermediate-level radioactive waste. (February 2021) - Jang, Sung-Chan; Woo, Hyunjong; Kim, Jeong-Guk; Lee, Dong-Ju; Kang, Il-Sik; Kim, Jongjin; Lee, Jin-Woo; Park, Won Jong; Park, Hee-Seoung
Highlights: An outlier and correlation analysis were carried out for 32 generation facilities. A outlier concentrations were determined in radioactive waste. There was a significant interaction in Cs-137 and Tc-99 according to the facility. Analyzing radionuclide data is an important factor for radwaste management. Abstract: In this paper, we collected the analysis data of radionuclide concentrations and performed verification analysis on the data integrity and outliers in radioactive waste. These analysis results investigated the correlation between the radionuclide concentration data. As a result of analyzing the characteristics and outliers of the radioactive waste radionuclide data by using the collected original and repackaged drum information, the several generation facilities with high average radionuclide concentrations were identified. As a result of discriminating radioactive concentration outliers by standardizing the values for each nuclide, it was confirmed that the I-129(2.45), Mn-54(2.31) and Nb-94(2.31) nuclides had outliers. Also, it was found that there was a significant interaction of concentration in the middle class of Cs-137 and Tc-99 according to the waste generation facility and middle-class classification. We expect to be able to efficiently manage and dispose the radioactive waste inventory through analyzing the radionuclide related data.